Analisis Kondisi Fear of Missing Out (FoMO) Mahasiswa Universitas Syiah Kuala - Putri Kurnia Rahmah; Nurbaity, Nurbaity; Rosita, Dara (Prodi Bimbingan dan Konseling Islam, 2025)
The FoMO phenomenon is observed to occur among students who actively use socialmedia. Students who experience FoMO tend to feel worried and anxious if they cannotparticipate in social activities or share their experiences on social media. This study aimsto describe the condition of Fear of Missing Out (FoMO) in Syiah Kuala UniversityStudents. The research approach uses descriptive data analysis techniques. Thisresearcher conducted a sampling technique through simple random sampling, whereeach member of the population had the opportunity to be selected as a sample. Thepopulation used in this study were Syiah Kuala University students. The study collecteddata from the USK student data portal which amounted to 23,700 students. The sampleof this study consisted of 394 students. The data collection technique used the Fear ofMissing Out (FoMO) scale. Data analysis techniques were carried out using descriptivestatistics. This study shows that based on the Fear of Missing Out (FoMO) scoreobtained. From these results, it can be concluded that the fear aspect has the highestpercentage (46.99%), followed by anxiety (36.14%), while worry has the lowestpercentage (16.87%). This shows that the majority of students are more likely toexperience FoMO in the form of fear of losing experience or information compared toanxiety or worry. FoMO conditions in the final students of Syiah Kuala University are ata moderate level, indicating the existence of FoMO conditions but not at a high level.